Policy Analysis of Restriction of Internet Access in The Region of Papua in 2019 in A National Security Perspective - Yusuf Syibly Ramadhan; Adis Imam Munandar (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2021)
The issue of racism that occurred in 2019 caused riots to erupt in the Papua region. The spread of hoaxes was one of the factors in the spread of riots so that the government issued a policy to restrict internet access but was later sued by the Southeast Asia Freedom of Expression Network (SAFEnet) Indonesia and the Alliance of Independent Journalists (AJI) to the PTUN and the result was that the government was found guilty for having committed an illegal act. This study analyzes the policy of restricting internet access in the Papua region in 2019 from a national security perspective using the Narrative Policy Framework (NPF) method. Although internet restrictions aim to create national security stability, this policy is not appropriate and its implementation is not in accordance with the mandate of the ITE Law so that as an alternative solution the government must prioritize early prevention and takedown actions that spread hoaxes or have the potential to threaten national security stability by synergizing all agencies government related.